Edukasi Anti Bullying: Strategi Pencegahan Bullying di SDIT Al-Hasanah dan SDN Kandang Panjang 03 - Sari Harahap, Angginun Juwita; Intan, Bella; Mustofa, Arya; Azhar, Agung; Khairunnisa, Rizky; Irman, Adi; Fajrin, Nurul; Ripki, Yuda; Nadwah, Izaazun; Ramadhandi, Simbar; Primarni, Amie; Maharani, Anissa (Jurnal Pengabdian West Science, 2025)
Bullying is a prevalent form of violence in schools, including elementary schools, with negative impacts on children’s psychological, social, and academic development. This phenomenon is also a global concern related to children’s right to safe and quality education. Olweus (1993) demonstrated the effectiveness of comprehensive intervention programs in reducing bullying incidents, while Smith et al. (2004) emphasized the crucial roles of teachers and school policies. In the Indonesian context, Suryani and Fithriani (2021) highlighted that culturally based approaches enhance the effectiveness of antibullying initiatives. This article explores the importance of early anti-bullying education in elementary schools, implementation strategies, challenges, and innovative solutions based on policies and educational practices. The study employs a systematic literature review of national and international research from 2000–2025. Findings indicate that anti-bullying education reduces violence, increases student empathy, strengthens parentteacher collaboration, and fosters a positive school climate.